Hybrid Nanocomposites of All‐Inorganic Halide Perovskites with Polymers for High‐Performance Field‐Effect‐Transistor‐Based Photodetectors: An Experimental and Simulation Study. Issue 18 (21st May 2022) - Sulaman, Muhammad; Yang, Shengyi; Song, Yong; Bukhtiar, Arfan; Hu, Jinming; Zhang, Zhenheng; Jiang, Yurong; Cui, Yanyan; Tang, Libin; Zou, Bingsuo
Abstract: All‐inorganic halide perovskites have recently emerged as a promising candidate for new‐generation optoelectronics. The device performance of solution‐processed photodetectors critically depends on the surface morphology and film features, however, the behind mechanism is not clear till now. In this paper, a feasible method for surface‐passivating all‐inorganic halide perovskites with poly(3‐hexylthiophene) (P3HT) as the photoactive layer for field‐effect transistor (FET)‐based photodetectors is presented, and the underlying mechanisms to enhance device performance are investigated by experimental and simulating study. As the result, a high photoresponsivity of 469 A W −1 with a specific detectivity of 1.34 × 10 14 Jones is obtained under 0.4 mW cm −2 405 nm illumination for FET‐based photodetector Au(S&D)/CsPbBr3 :P3HT/PMMA/Al(G). This experimental and simulating study shows that the enhanced‐performance origins from improving the photogenerated charge carriers transportation and suppressing the dark current through the photodetectors. Abstract : In order to solve the critical issues about the structural defects of the halide perovskites layer, a feasible and attractive approach for the surface passivation of CsPbBr3 NCs by blending with Poly(3‐hexylthiophene) (P3 HT) to form a bulk‐heterojunction as the photoactive layer for high‐performance FET‐based photodetectors Au(S&D)/CsPbBr3 :P3 HT/PMMA/Al(G) is presented. The physical mechanisms for photogenerated carriers' transportation are discussed in details.